Perlindungan Hukum Terhadap Anak Dalam Praktik Pernikahan Dini Adat Desa Golo Kondeng Kabupaten Manggarai Barat - Florentina Fitriano (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
Early marriage remains a social issue occurring in various regions, including Golo Kondeng Village, West Manggarai Regency, East Nusa Tenggara Province. This study aims to examine the form of legal protection afforded to the status of children born from early marriages conducted based on local customary law. This research employs a qualitative approach with a case study method, collecting data through in-depth interviews with community leaders, parents, and relevant village authorities. The findings indicate that early marriage practices in Golo Kondeng Village are influenced by several factors, including cultural values, family economic conditions, and the community’s level of education. Although existing laws—such as Law Number 16 of 2019, which amends Law Number 1 of 1974 on Marriage by establishing the minimum marriage age at 19 for both men and women, and Law Number 35 of 2014 on Child Protection—clearly regulate the legal age for marriage, the reality shows that early marriages continue to occur, often neglecting the fulfillment of children’s rights. The current legal protections are not yet fully effective in securing the legal status of these children, both in terms of civil and social rights. Based on these findings, this study recommends enhancing legal education and outreach to the community regarding marriage laws and children's rights. In addition, the active involvement of traditional leaders and local government is considered essential in addressing the issue of early marriage. It is hoped that through these efforts, children born from early marriages can receive adequate legal protection and have their rights fully fulfilled.